Harmonisation of Malaysian partnership law and Shari'ah law with regard to rights and liabilities of partners - Masoodeen, Mohamed Lafeer Zainul (Ahmad Ibrahim Kulliyyah of Laws, International Islamic University Malaysia, 2022)
The relevant provisions of the Malaysian Partnership Act 1961, built upon English Partnership Act 1890, have been scrutinized in terms of rights and liabilities of partners by undertaking a comparative investigation with the Shari‘ah in order to identify inconsistencies between them so as to propose measures aimed at minimizing conflicts to an extent possible. The analysis has exposed that, despite the majority of the provisions of the Act being in conformity with the Islamic rules of partnership, their interpretation espoused by the courts appear to be in need of reconciliation. In devising a suitable mechanism to reconcile, the process of harmonization is adopted based on the recommendations of Shari‘ah scholars. The study primarily relies on Malaysian case laws and case laws from Common Law jurisdictions, juristic opinions and academic writings while employing library based research methodology. The proposed process of harmonization can fulfill the underlying aim of the Shari‘ah due to the existence of complimentary relationship between Common Law rulings and the Shari‘ah principles within the range of the research title. As the study, limited to the title, could figure out incompatibility between the two laws, the thesis proposes amendments to the Malaysian Partnership Act by applying the process of harmonisation. Finally, a practical approach towards removing certain conflicts in the areas such as sharing fixed sum profits, sharing loss equally among partners, paying remuneration for active partners and some other relevant stipulations and suggesting recommendations to harmonise the incompatibility between the two laws.